Sebagai syarat untuk KOMPRE PEMETAAN PERSEBARAN KAWASAN KELOMPOK TANI HUTAN (KTH) BERBASIS KAUM DI NAGARI PASIA LAWEH KECAMATAN PALUPUH, KABUPATEN AGAM - khaidir ilqam ramadhan (JURNAL BUANA, 2022)
ABSTRACT This study aims to: 1) find out how the distribution and extent of the community-based Forest Farmers Group area in Nagari Pasia Laweh. 2) determine land tenure by the people in Nagari Pasia Laweh, and 3) find out changes in land use from 2015 to 2020 in Nagari Pasia. Laweh.This type of research uses quantitative methods. The data collection techniques include the process of measuring and taking data directly to the field using a GPS (Global Positioning System). Sources of data from this study using primary data obtained and collected by researchers directly in the field and using secondary data obtained from journals and related agencies. This study found: 1) The distribution and extent of forest farmer groups spread over seven jorongs, including Jorong Sungai Guntuang, Pasia Laweh, Palupuah, Aur Kuning, Lurah Dalam, Angge and Palimbatan with the highest area being in KTH Kaum Datuak Manjuang Basa with an area of ​​16 Ha, while the lowest KTH area is in Jorong Pasia Laweh with an area of ​​0.6 Ha. 2) Land tenure by people. From observations obtained by secondary data, it shows that in several jorongs there are slight changes, either changes in the direction of decreasing or increasing, due to several factors, including: (a) there is a sale and purchase transaction for the Forest Farmer Group Area, (b) there is a division of inheritance that causes a people to increase or decrease the land they own. (c) the existence of land use that was originally as agricultural land changed to other land uses. 3) The dynamics of land use from 2015-2020 from the results obtained through a GIS analysis of land use in 2015 in Nagari Pasia Laweh shows that almost 80% of the Group Area Forest Farmers still have green open space vegetated land with the highest dominance being shrubs in 2015 dominated by shrubs with an area of ​​13.06 ha or 57% of the total area after 5 years in 2020 the widest land use is in mixed gardens with 17.65 ha or 41% of the total area in 2015 and 2020. Keywords: Distribution & Area, Control, Land Use Change